Revisiting the bi-factor structure of the short version of the Warwick–Edinburgh mental well-being scale with samples in China - Fung, Sai-fu; Zeng, Guang; Chuang, Ho-luan Hermes; Li, Sin-man; Lee, Jingwen; Tse, Jonathan Chun Luen (Frontiers in Psychology, 2025)
AimThis paper aims to evaluate the factor structure and psychometric properties of the Short Warwick-Edinburgh Mental Well-being Scale (SWEMWBS) based on Chinese samples recruited from secondary schools, universities, and workplaces.MethodsThe psychometric properties of the SWEMWBS were evaluated in four cross-sectional studies with a total of 1,729 respondents from Hong Kong and Chinese mainland. Criterion validity was assessed using well-established measures of well-being, affect, and life satisfaction (PANAS, WHO-5, and SWLS). Confirmatory factor analysis was employed to evaluate the unidimensional and bi-factor structure of the SWEMWBS.ResultsThe results indicated that both the Traditional and Simplified Chinese versions of the SWEMWBS possess good psychometric properties, with coefficient alpha and omega exceeding the acceptable range. Both exploratory factor analysis and confirmatory factor analysis suggested that the items are suitable for forming a unidimensional scale. However, the bi-factor structure proposed in the recent literature contained some problematic items that yielded negative and weak factor loadings.ConclusionThe unidimensional SWEMWBS is applicable to respondents from diverse socio-economic and cultural backgrounds. The validated Traditional and Simplified Chinese versions of the SWEMWBS provide researchers and clinical practitioners with a reliable and convenient measure of mental well-being for use in Chinese contexts.